PENGARUH KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) (Studi pada Karyawan Kantor Konsultan Manajemen Rizqi) - Tantri Widiastuti; Suaris Suaris (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2017)
This study aimed to analyze the effect of Organization Commitment and Job Satisfaction on OCB. The data used in this study was primary data obtained from questionnaires. Total samples were 63 respondents who constituted the entirety of the population of Consultant Office Manajemen Rizqi (Tax and Management Consultant) so it used census samples. The analysis technique used was multiple regression method and hypothesis testing using F test and t test. The results showed that variable Organization Commitment had positive and significant effect on OCB. Variable Job Satisfaction had positive and significant effect on OCB. And the variable that had the most dominant effect on OCB was variable Organization Commitment. From this study it obtained R2 value of 0.429, meaning that 42,9% of OCB variable could be explained by independent variable.The remaining 57,10% were explained by other variables outside the research